Nourrir les morts – les poteries associées aux défunts dans le cimetière néolithique KDK23 (ve millénaire av. J.-C., Soudan) - Philippe Chambon; Pascal Sellier; Aline Emery-Barbier; Olivier Langlois (Revue d'ethnoécologie)
In the area of Kadruka, in Sudanese Nubia, almost twenty Neolithic cemeteries from the Vth millennium BC have been identified. The current excavation at KDK 23 has already provided more than 130 burials, almost all individual. The often plentiful goods consisted in unused objects or even objects made for the funeral itself, except for the ceramic pots that played a specific role. Taken from the household, they are mainly containers; the inclusion of additional items such as spoons, small bowls or feeding bottles, inside pots associated with infants indicates that they indeed contained food for the dead; supplies for the last journey.